2019
DOI: 10.1016/j.aca.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the retention factor of ionizable compounds in microemulsion electrokinetic chromatography

Abstract: Determination of the retention factor of ionized compounds in microemulsion electrokinetic chromatography requires two mobility measurements at the same pH: one in the presence of the microemulsion and another in plain buffer. However, it has been observed that in some cases subtracting one mobility from another determined in a different medium leads to negative retention factors, which makes no sense from a chemical point of view. This indicates that there is some error in the process which has a direct impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…However, the MEEKC medium contains not only the aqueous buffer but also the surfactant, the co-surfactant and the oil, which usually have viscosities very different from water. Thus, the presence of ME components changes the viscosity of the medium, leading to inaccurate k values, as demonstrated in previous work [18]. Note that the viscosity of the electrophoretic medium (ƞ) and the mobility of a compound are inversely related, according to Eq.…”
Section: Calculation Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the MEEKC medium contains not only the aqueous buffer but also the surfactant, the co-surfactant and the oil, which usually have viscosities very different from water. Thus, the presence of ME components changes the viscosity of the medium, leading to inaccurate k values, as demonstrated in previous work [18]. Note that the viscosity of the electrophoretic medium (ƞ) and the mobility of a compound are inversely related, according to Eq.…”
Section: Calculation Methodsmentioning
confidence: 75%
“…Experimental k-pH profiles of the compounds were taken from a previous study [18] and the log k-pH profiles were obtained by fitting the data to Eq. 11.…”
Section: Influence Of the Degree Of Ionization On The Estimation Of Log Do/wmentioning
confidence: 99%
“…In a previous work [14], we studied the effect of the ionization of acids in a MEEKC system with a ME composed of heptane, 1-butanol and sodium dodecyl sulfate (SDS, an anionic surfactant), a system which showed to be a good surrogate for the determination of octanol-water partition coefficients [6][7][8][9][10]. However, the study of the retention of partially protonated bases was not intended because additional interactions, other than partition of the unionized form of the base into the ME, were expected.…”
Section: Introductionmentioning
confidence: 90%
“…However, it is clear that micellar and microemulsion systems have different properties. For instance, we have demonstrated that the addition of the oil and cosurfactant, needed to form the microemulsion, change significantly the viscosity of the surfactant solution and the usual MEKC equation used to calculate the retention factor of partially ionized acids has to be corrected for this change of viscosity [14]. Also, the solvation properties of MEKC systems strongly depend on the surfactant used to form the micelle [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation